2016
DOI: 10.1007/s11899-016-0306-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Long-Term Therapy in Patients with Chronic Myeloid Leukemia

Abstract: Since the development of imatinib and other tyrosine kinase inhibitors (TKIs), the prognosis for patients with chronic myeloid leukemia (CML) has markedly improved, such that most patients diagnosed with CML can now expect to live with their disease rather than die from it. However, most patients will require long term treatment, which has deleterious effects on health-related quality of life. We review recent literature on drug-related adverse effects, long term medication adherence, limitations to fertility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 39 publications
(40 reference statements)
1
35
0
Order By: Relevance
“…chronic myeloid leukaemia, medication adherence, medication information, patients' experiences, qualitative research, tyrosine kinase inhibitors effects including myelosuppression, rash, nausea, diarrhoea, fatigue, and musculoskeletal pain or myalgia. 5,6 The nature and frequency of these adverse effects varies depending on the TKI. TKI treatment is continued until progression of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…chronic myeloid leukaemia, medication adherence, medication information, patients' experiences, qualitative research, tyrosine kinase inhibitors effects including myelosuppression, rash, nausea, diarrhoea, fatigue, and musculoskeletal pain or myalgia. 5,6 The nature and frequency of these adverse effects varies depending on the TKI. TKI treatment is continued until progression of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Proton pump inhibitors are generally contraindicated in combination with TKIs, and medications associated with QT prolongation require increased ECG monitoring while receiving TKI M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT therapy. 12 This frequent monitoring and concern over concomitant medications can be both inconvenient and challenging for a patient. Moreover, long-term TKI therapy can be problematic for patients interested in conceiving.…”
Section: Why Stop Tkis?mentioning
confidence: 99%
“…As it appears unlikely that even a sustained remission truly indicates a complete eradication of the leukemic cells, other factors have to account for a continuing control of a minimal, potentially undetectable residual leukemic load. Although treatment discontinuation is highly desirable to reduce treatment-related side-effects and lower financial expenditures (16)(17)(18)(19), it is still not possible to prospectively identify those patients that are at risk for a molecular recurrence. Investigations of clinical markers and scores to predict the recurrence behavior of patients after the treatment cessation revealed that both TKI treatment duration and the duration of a DMR were also associated with a higher probability of TFR (11,15,20,21).…”
Section: Introductionmentioning
confidence: 99%